Alexander Alekseevich Vybornov Is 70 Years Old! - Konstantin M. Andreev; Olga V. Andreeva; Natalia S. Doga; Evgeniia Р. Tkach (Археология евразийских степей)
On October 21, 2024, Alexander Alekseevich Vybornov turns 70. He devoted most of his life to studying the Stone Age of the Volga-Kama region and adjacent territories. The proposed note is devoted to the description of the main milestones of the birthday boy's scientific activity. Information is provided about his work at the history department of the Kuibyshev / Samara Pedagogical University. The main stages of field expeditionary activities aimed at studying archaeological monuments in the vast territory of the European part of Russia are noted. Information is provided on the scientific and organizational work of the hero of the day, preparation and participation in numerous conferences and supervision of the writing of dissertations. The key areas of scientific work of Alexander Alekseevich and the topics of the most significant articles and monographs.